2012
DOI: 10.1089/jwh.2011.2764
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Dose Titration and Dose Tapering on the Tolerability of Desvenlafaxine in Women with Vasomotor Symptoms Associated with Menopause

Abstract: Titration regimens may improve tolerability of desvenlafaxine 100 mg/d in postmenopausal women with VMS. Taper regimens of desvenlafaxine 50 mg/d-placebo or 50/25-mg/d, were better tolerated than abrupt discontinuation or desvenlafaxine 50 mg given every other day taper regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…Comparisons of Different Discontinuation Methods Two studies evaluated the tolerability of different discontinuation methods after treatment of major depression [7] and vasomotor symptoms in healthy postmenopausal women [36]. After the RCT phase, all treatments were interrupted and a follow-up evaluation was done to evaluate discontinuation symptoms (online suppl.…”
Section: Single Drug At Different Doses Comparisonsmentioning
confidence: 99%
“…Comparisons of Different Discontinuation Methods Two studies evaluated the tolerability of different discontinuation methods after treatment of major depression [7] and vasomotor symptoms in healthy postmenopausal women [36]. After the RCT phase, all treatments were interrupted and a follow-up evaluation was done to evaluate discontinuation symptoms (online suppl.…”
Section: Single Drug At Different Doses Comparisonsmentioning
confidence: 99%
“…One study found symptoms considered to represent withdrawal in 45% of subjects being treated for panic disorder after 2 or more weeks of discontinuing a variety of SRIs, though without a comparison group involving abrupt or rapid discontinuation [40]. Another trial evaluated withdrawal symptoms after discontinuing desvenlafaxine in older women treated for menopausal vasomotor instability, with randomization to abrupt discontinuation or to various stepwise reductions of doses over 2 weeks; the findings supported a ­reduction of risk of withdrawal symptoms with more gradual discontinuation [41]. A third study of anxiety disorder patients found that antidepressants could be ­discontinued, even very slowly over 4 months, in only 37%, and that two-thirds became newly anxious [42].…”
Section: Withdrawal Reactionsmentioning
confidence: 99%
“…A recent published well-written review also concluded that desvenlafaxine at doses of 100 mg have not been shown to cause significant side effects [28]. Furthermore, dose titration improved tolerability of desvenlafaxine 100 mg and resulted in a low rate of discontinuations due to adverse effects [14]. The desvenlafaxine dose should be titrated appropriately to minimize the chance of treatment discontinuation.…”
Section: Discussionmentioning
confidence: 99%
“…Several non-hormonal compounds including clonidine, gabapentin, and some of serotonin and serotonin-norepinephrine reuptake inhibitors have been used for relief of VMS. Desvenlafaxine, a novel serotonin norepinephrine reuptake inhibitor, has been shown to be effective for the treatment of moderate to severe hot flashes associated with menopause [11,12,13,14,15,16,17,18]; however, the results have not been entirely consistent [19]. There have been potential cardiovascular risks associated with the use of desvenlafaxine in this patient population [11].…”
Section: Introductionmentioning
confidence: 99%